Pengaruh Model Stad Berbantuan Peta Konsep Digital Canva Terhadap Pemahaman Konsep IPS Siswa - Sahrul Hidayat; Nurdiansyah Nurdiansyah; Tiara Yogiarni (LPPM Institut Pendidikan Nusantara Global, 2026)
Conceptual understanding in social studies is an essential competency for elementary school students to comprehend social phenomena meaningfully. However, many students still demonstrate low conceptual understanding due to teacher-centered learning and limited use of innovative instructional media. This study aims to analyze the effect of the Student Teams Achievement Division (STAD) model assisted by Canva-based digital concept maps on students' conceptual understanding in social studies. This research employed a quasi-experimental approach with a nonequivalent control group design. The subjects were fourth-grade students of SDN 9 Nagrikaler, divided into experimental (34 students) and control groups (32 students). The instrument consisted of 20 multiple-choice questions analyzed using IBM SPSS version 29. The results showed a significant difference between groups with a posttest significance value of 0.011 < 0.05. The mean posttest score of the experimental group was 83.09, higher than the control group at 72.81. The N-Gain score of the experimental group was 53.46 (moderate), higher than the control group at 38.00 (moderate). Regression analysis showed F = 64.415 (p < 0.001) with R² = 0.502, indicating STAD contributed 50.2% to the improvement of social studies conceptual understanding. These findings indicate that the STAD model assisted by Canva digital concept maps has a positive and significant effect.